The Effects of the Covid-19 Pandemic on Kuwaiti Kindergarten Staff to Adopt E-Learning System - Ashkanani, Alia; Tamtam, Abdalmonem (European Scientific Journal, ESJ, 2021)
E-learning has been implemented on a mass scale during the COVID-19 crisis although many schools faced huge problems during the system implementation and roll-out. This paper has used the technology acceptance model (TAM) to investigate the teachers and administrative staff’s prospective on the use of e-learning in the education process. The study has implemented a quantitative method to collect data through a questionnaire. The study had 204 participants which included teachers and administrative staff in kindergartens under the Kuwaiti Ministry of Education (MOE). The study showed that the majority of the participants were not in favor of e-learning as the system was neither clear nor it was understandable or flexible, which hindered teachers work. The Ministry of educations strategy to bring e-learning to the mass users was undermined due to unclear strategic objective and lack of proper training and support that stood as a barrier to users’ acceptance of e-learning.